Research in economic history - Kantor, Shawn; Kitchens, Carl T. (Emerald Publishing Limited, 2025)
In this new volume of Research in Economic History, editors Shawn Kantor and Carl T. Kitchens bring together a diverse range of expert contributors to vigorously interrogate and analyse historic economics questions. This includes examinations of inequality from North and South America, as well as Europe, in terms of health, land, and wealth. For researchers and students of economic history, this volume pulls together the latest research on a variety of unanswered questions from the 1860s until the present day.
Includes index.
Keywords: Economic history.; Business & Economics -- Economic History.; elektronické knihy; electronic books